(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cardiovascular diseases are a group of disorders of the heart and main blood vessels in which the excess blood cholesterol is deposited as fatty streaks or plaque along the vessel wall thereby obstructing the flow of blood through those arteries. Atherosclerosis is the beginning of cardiovascular diseases. About 47% of the Indian population dies from cardiovascular diseases. Above 615,000 people in the United States are dying from cardiovascular diseases every year. There are various behavioral, environmental, and psychological factors that play a role in the formation of atherosclerosis. But the other most important factor is Indian dietary edible vegetable oils including mustard oil, coconut oil, sesame oil, soybean oil, sunflower oil, rice bran oil, palm oil, olive oil, and fish oils such as mackerel fish oil, salmon fish oil, tuna fish oil, cod liver oil shark liver oil which contains several fatty acids for example- butyric acid, caproic acid, lauric acid, myristic acid, palmitic acid, oleic acid, palmitoleic acid, alpha-linolenic acid, gamma-linoleic acid, arachidonic acid, docosahexaenoic acid, docosapentaenoic acid, eicosapentaenoic acid which plays very important roles on cardiovascular health.